Dual role for Fcγ receptors in host defense and disease in Borrelia burgdorferi-infected mice - Belperron, Alexia A.; Liu, Nengyin; Booth, Carmen J.; Bockenstedt, Linda K. (Frontiers in Cellular and Infection Microbiology, 2014)
Arthritis in mice infected with the Lyme disease spirochete, Borrelia burgdorferi, results from the influx of innate immune cells responding to the pathogen in the joint and is influenced in part by mouse genetics. Production of inflammatory cytokines by innate immune cells in vitro is largely mediated by Toll-like receptor (TLR) interaction with Borrelia lipoproteins, yet surprisingly mice deficient in TLR2 or the TLR signaling molecule MyD88 still develop arthritis comparable to that seen in wild type mice after B. burgdorferi infection. These findings suggest that other, MyD88-independent inflammatory pathways can contribute to arthritis expression. Clearance of B. burgdorferi is dependent on the production of specific antibody and phagocytosis of the organism. As Fc receptors (FcγR) are important for IgG-mediated clearance of immune complexes and opsonized particles by phagocytes, we examined the role that FcγR play in host defense and disease in B. burgdorferi-infected mice. B. burgdorferi-infected mice deficient in the Fc receptor common gamma chain (FcεRγ−/− mice) harbored ~10 fold more spirochetes than similarly infected wild type mice, and this was associated with a transient increase in arthritis severity. While the elevated pathogen burdens seen in B. burgdorferi-infected MyD88−/− mice were not affected by concomitant deficiency in FcγR, arthritis was reduced in FcεRγ−/−MyD88−/− mice in comparison to wild type or single knockout mice. Gene expression analysis from infected joints demonstrated that absence of both MyD88 and FcγR lowers mRNA levels of proteins involved in inflammation, including Cxcl1 (KC), Xcr1 (Gpr5), IL-1beta, and C reactive protein. Taken together, our results demonstrate a role for FcγR-mediated immunity in limiting pathogen burden and arthritis in mice during the acute phase of B. burgdorferi infection, and further suggest that this pathway contributes to the arthritis that develops in B. burgdorferi-infected MyD88−/− mice.